Fibroadenoma of ectopic breast tissue in chest wall: a rare case report and review of the literature - Balmiki, Pradeep; Mourya, Kamlesh (International Surgery Journal, 2019)
Fibroadenoma of ectopic breast tissue is a rare disease. Ectopuc breast tissues are found along milk line. Malignancy is more common than fibroadenoma in ectopic breast tissue. Ectopic breast tissue can be present with nipple or without nipple areola complex. Here we report a case of 20 years old patient having fibroadenoma of ectopic breast tissue in anterior chest wall without nipple areola complex. Patient underwent excision and biopsy. Histopathology confirmed it as fibroadenoma of the ectopic breast tissue. This case has been reported for its rarity and to reemphasise the importance of screening of EBT for any pathology during routine screening of breast.